Elevated GlycA in severe obesity is normalized by bariatric surgery. Issue 1 (28th August 2018) - Manmadhan, Arun; Lin, Bing‐Xue; Zhong, Judy; Parikh, Manish; Berger, Jeffrey S.; Fisher, Edward A.; Heffron, Sean P.
Abstract : Chronic inflammation drives many obesity‐associated conditions including atherosclerosis. GlycA, a marker of systemic inflammation with lower intra‐individual variability than high sensitivity C‐reactive protein, is independently associated with incident cardiovascular events and mortality. Although GlycA is elevated in obesity, correlations with anthropometric measures are modest and the effect of body weight loss on GlycA is untested. Obese (body mass index [BMI] 44.6 ± 6.6 kg/m 2 ), non‐diabetic women (33.7 ± 8.2 years) undergoing Roux‐en‐Y gastric bypass (n = 23) or sleeve gastrectomy (n = 31) were prospectively studied at baseline, 6 and 12 months postprocedure. Women with normal BMI (n = 14) served as controls. Bariatric surgery significantly reduced GlycA by 6 months (451 ± 47 μmol/L vs. 383 ± 50 μmol/L; P < 0.001) with further reduction at 12 months (348 ± 41 μmol/L; P < 0.001) and no difference between procedures. At 12 months, despite 41% of surgical subjects maintaining BMI >30 kg/m 2, GlycA levels did not differ between surgical and control subjects ( P = 0.13). Increased high density lipoprotein particle size was strongly associated with reduced GlycA (r = −0.49; P < 0.001) and was found to mediate up to 43% of its body weight‐loss‐associated fall. This is the first study to demonstrate that surgical body weight loss markedly reduces levels of GlycA.